First large‐scale quantification study of DNA preservation in insects from natural history collections using genome‐wide sequencing. Issue 2 (17th August 2022) - Mullin, Victoria E.; Stephen, William; Arce, Andres N.; Nash, Will; Raine, Calum; Notton, David G.; Whiffin, Ashleigh; Blagderov, Vladimir; Gharbi, Karim; Hogan, James; Hunter, Tony; Irish, Naomi; et al.
Abstract: Insect declines are a global issue with significant ecological and economic ramifications. Yet, we have a poor understanding of the genomic impact these losses can have. Genome‐wide data from historical specimens have the potential to provide baselines of population genetic measures to study population change, with natural history collections representing large repositories of such specimens. However, an initial challenge in conducting historical DNA data analyses is to understand how molecular preservation varies between specimens. Here, we highlight how Next‐Generation Sequencing methods developed for studying archaeological samples can be applied to determine DNA preservation from only a single leg taken from entomological museum specimens, some of which are more than a century old. An analysis of genome‐wide data from a set of 113 red‐tailed bumblebee Bombus lapidarius specimens, from five British museum collections, was used to quantify DNA preservation over time. Additionally, to improve our analysis and further enable future research, we generated a novel assembly of the red‐tailed bumblebee genome. Our approach shows that museum entomological specimens are comprised of short DNA fragments with mean lengths below 100 base pairs (BP), suggesting a rapid and large‐scale post‐mortem reduction in DNA fragment size. After this initial decline, however, we find a relatively consistent rate of DNA decay in our dataset, and estimate a mean reduction in fragment length of 1.9 bp per decade. The proportion of quality filtered reads mapping to our assembled reference genome was around 50%, and decreased by 1.1% per decade. We demonstrate that historical insects have significant potential to act as sources of DNA to create valuable genetic baselines. The relatively consistent rate of DNA degradation, both across collections and through time, mean that population‐level analyses—for example for conservation or evolutionary studies—are entirely feasible, as long as the degraded nature of DNA is accounted for.